Night shift work and cardiovascular diseases among employees in Germany: five-year follow-up of the Gutenberg Health Study - Sylvia Jankowiak; Karin Rossnagel; Juliane Bauer; Andreas Schulz; Falk Liebers; Ute Latza; Karla Romero Starke; Andreas Seidler; Matthias Nübling; Merle Riechmann-Wolf; Stephan Letzel; Philipp Wild; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVE: This study aimed to determine if there is an increased risk of incident cardiovascular diseases (CVD) resulting from cumulative night shift work in the German population-based Gutenberg Health Study (GHS). METHODS: We examined working participants of the GHS at baseline and after five years. Cumulative night shift work in the 10 years before baseline was assessed and categorized as low (1-220 nights ≙ up to 1 year), middle (221-660 nights ≙ 1-3 years), and high (>660 nights ≙ more than 3 years) night shift exposure. Hazard ratios (HR) were estimated for incident "quality-assured CVD events" using Cox proportional hazard models. RESULTS: At baseline, 1092 of 8167 working participants performed night shift work. During the follow-up, 202 incident cardiovascular events occurred. The crude incidence rates for CVD per 1000 person-years were 6.88 [95% confidence interval (CI) 4.80-9.55] for night shift workers and 5.19 (95% CI 4.44-6.04) for day workers. Cumulative incidence curves showed a higher cumulative incidence in workers exposed to night shift work compared to day workers after five years. The adjusted HR for incident CVD events were 1.26 (95% CI 0.68-2.33), 1.37 (95% CI 0.74-2.53) and 1.19 (95% CI 0.67-2.12) for employees in the low, middle and high night shift categories compared to employees without night shift work, respectively. CONCLUSIONS: The observed tendencies indicate that night shift work might be negatively associated with cardiovascular health. We expect the continued follow-up will clarify the long-term impact of night shift work.